Assessment of dental caries and periodontal status in institutionalized hearing impaired children in Khordha District of Odisha - Avinash Jnaneswar; Goutham Bala Subramaniya; Jayashree Pathi; Kunal Jha; Vinay Suresan; Gunjan Kumar (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2017)
Introduction: Over 5% of the world's population has disabling hearing loss. The oral health of the disabled may be disused for the reason of the disabling condition, a challenging disease or the limited access to oral health care. Objectives: The objectives of the study were to assess the prevalence of dental caries and periodontal status of institutionalized hearing impaired (HI) children in Khordha district of Odisha. Materials and Methods: A descriptive cross-sectional study on the HI children was conducted in Khordha district, Odisha. Type III examination procedure was conducted to assess the oral health status of the children. Statistical analysis was performed by Chi-square test and Student's t-test, and the significance level was fixed at P < 0.05. Results: The final population consisted of 540 HI children out of which 262 (48.5%) were male and 278 (51.5%) were female, 285 (52.8%) children had severe hearing loss and 227 (42.0%) had profound hearing loss. Bleeding on probing was found in 72 (13.3%) female children as compared to 57 (10.6%) male children. While 131 (24.3%) female children had calculus, 124 (23.0%) male children had the same condition. Total caries prevalence was 19.3%. Statistically highly significant difference was found for mean decayed teeth (DT), missing teeth decayed, missing filled teeth (FT) (P < 0.001), while for mean FT there was no statistically significant difference according to age groups. Statistically highly significant difference was found for mean DT, extracted teeth and decayed, extracted, filled teeth (P < 0.001). Conclusion: An improved accessibility to dental services as well as dental health education is necessary to ensure the optimum dental health within the reach of these less fortunate children.